Plot Structures in A Novel Entitled the Suitcase Kid Written by Jacqueline Wilson (An Analysis with A Narratological Approach) - Siti Aisyah Saraswati Rusdi (Passage, 2016)
This present research aims to analyze the plot structures in Jacqueline Wilson’s novel entitled The Suitcase Kid (1992) by using Narratology. This qualitative research focuses on the plot of the story in order to analyze how the plot of the story is structured in the novel and to construct the meaning that can be made from the structure of the plot. The findings of this research reveal that the plot of the story is structured like a tree. The plot is developed by a major plot which gives ways for five interrelated plots and forms a story with branching plots. The finding indicates that there are two potential meaning which originated by the structure of the plot. Firstly, the story with branching plots elevates the level of suspense to the reader. Secondly, the set of events in the novel indicates that The Suitcase Kid can be considered as a Bildungsroman novel.